Revision of the genus Tillicera Spinola, 1841 (Coleoptera: Cleridae, Clerinae) - Gerstmeier, Roland; Bernhard, Nadine (Zootaxa, 2010)
The genus Tillicera Spinola, 1841 is taxonomically revised to include fifteen species with the following species described as new: Tillicera callosa, Tillicera michaeli, Tillicera obscura, Tillicera pseudocleroides and Tillicera tonkinensis. Tillicera mimomutilla Pic, 1926 n. syn. and Dasyceroclerus rouyeri Pic, 1938 n. syn. are placed in synonymy with Tillicera cleroides Gorham, 1892, and Tillicera hirsuta (Pic, 1926) n. comb., is transferred from Thanasimus Latreille. A key to species is provided.